Kajian Yuridis Tentang Pemberhentian Tidak Dengan Hormat (PTDH) Anggota Kepolisian Rupublik Indonesia dalam Prespektif Hukum Administrasi Negara - Prakoso, Aditya Afieq; Moonti, Roy Marthen; Amu, Robby W.; Kasim, Muslim A. (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This research examines the legal certainty of Dishonorable Dismissal (Pemberhentian Tidak Dengan Hormat/PTDH) for members of the Indonesian National Police, considering its significant impact on employment status, administrative rights, and professional dignity. The study aims to analyze the normative regulation of PTDH and evaluate its implementation based on Administrative Law principles, including legality, authority, procedure, the General Principles of Good Governance, and legal protection. This research employs a normative legal method with a qualitative approach through literature studies of statutory regulations, legal doctrines, and relevant court decisions concerning PTDH disputes. The findings reveal that PTDH regulations have a sufficient legal foundation through the Law on the Indonesian National Police, Government Regulations on police member dismissal, the Law on Government Administration, and Police Regulations concerning the Professional Code of Ethics. However, implementation remains problematic due to inconsistencies in sanction enforcement, limited transparency, inadequate protection of defense rights, and potential violations of good governance principles. These findings indicate a gap between existing legal norms and administrative practices. Therefore, strengthening standard operating procedures, ensuring objective examination processes, guaranteeing administrative appeal rights, clarifying legal considerations in decisions, and optimizing internal and judicial supervision are necessary to ensure PTDH is carried out fairly, proportionally, transparently, and accountably within the framework of a rule-of-law state.